Incorporating agro-biodiversity to market-oriented organic rice in Northern Thailand: An enabling innovation process and achievement - Budsara Limnirankul (2018)
The greatest challenge to organic agriculture is for the system to become sustainable in economic, ecological and social dimensions in time of uncertainty. This paper draws on working experiences with the transitions to market-oriented organic rice in Chiang Mai province, Northern Thailand. We outline how smallholder farmers make decisions towards organic rice and at the same time, incorporate rice biodiversity, and improve agronomic performance, entrepreneurial skills and competences through multi-level social interactions. We employed supervised and unsupervised learning approaches to document how smallholder farmers incorporate agro-biodiversity in their organic farming design. The study covered farmer groups in Chiang Mai Valley with varying experiences and scale of operation. It focused on farmers' perception on agro-biodiversity, its functionality, and decision to incorporate it into organic rice system, as well as the outcome. We observed several farmer innovations of utilizing agro-biodiversity to stabilize productivity and enhance farm income. Three genetically diverse rice varieties with different processing techniques were produced to increase value addition. Farmers tested rice varieties for site specific adaptation before embarked on large scale production. They also modified and adapted dry seeded rice technique to improve water management and reduce production cost. We studied the trading partnership between farmer groups and organic farmer-cum-trader through contract arrangement to see how social mechanism makes contract farming work for smallholder farmers. Despite several obstacles faced by farmers during the transition to organic rice, we conclude that incorporating rice biodiversity in organic system provides a starting point for farmers to value functionality of agro-biodiversity.